Linking Ionic Composition to Salinity-Driven Soil Degradation in Arid Agroecosystems of Uzbekistan - Atoeva, D. O. (American Journal of Biology and Natural Sciences, 2026)
Soil salinization is a major environmental process driving land degradation in arid ecosystems, significantly altering soil chemical balance and ecosystem stability. This study investigates ionic composition and salinity-induced soil degradation processes in arid soils of the Bukhara region, Uzbekistan, with a focus on understanding the mechanisms governing soil quality decline. Soil samples collected from the 0–30 cm layer were analyzed for electrical conductivity (ECe), pH, organic matter content, macro-nutrients, and detailed ionic composition using standard agrochemical methods and energy-dispersive X-ray fluorescence (EDXRF). The results revealed moderate to very high salinity levels (5.20–8.12 dS/m) and slightly alkaline conditions (pH 7.6), indicating unfavorable chemical environments for sustainable soil functioning. Ionic analysis confirmed the dominance of sodium (Na⁺) and chloride (Cl⁻) ions, indicating chloride-type salinization. Elevated sodium concentrations contribute to soil structural degradation, reduced permeability, and disruption of nutrient exchange processes. Despite moderate organic matter content ( 1.07%), soils exhibited low total nitrogen and potassium levels, along with critically low available phosphorus, reflecting severe nutrient imbalance under salinity stress. This study provides new insights into salinity-driven soil degradation processes in arid regions and contributes to the development of sustainable land management strategies in Central Asian dryland ecosystems.